Peloponnesian War Perpetual Conflict and Future Challenges - Musayyab, Said; Soemantri, Asep Iwa; Prakoso, Lukman Yudho (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The Peloponnesian War, a monumental conflict in ancient Greek history, provided much valuable knowledge for modern foreign policy. Through an analysis of conflict-inducing factors, the military and political strategies used by Athens and Sparta, and their implications for the future, this article highlights the importance of diplomacy, strong alliances, balance of power, and effective military strategy in preventing conflict and promoting peace. Recommendations are given to prioritize diplomacy, strengthen regional alliances, respect the balance of power, collaborate multilaterally, and maintain flexibility and adaptation in foreign policy. The methodology used in this article is a comprehensive literature study on the topic of the Peloponnesian War. By applying knowledge from the Peloponnesian War, nations can build a solid foundation for future peace, stability, and prosperity, drawing lessons from history to shape a better future for all humanity.